Online Plagiarism Detection Tools in the Digital Age: A Review - Chandere, Vandana; Satish, S; Lakshminarayanan, R (Annals of the Romanian society for cell biology, 2021)
The main objectives of these regulations are : * To create awareness regarding the conduct of research, dissertations, project work, assignments, and thesis including plagiarism among the academic and scientific community * Set up an institutional mechanism through education and training to facilitate responsible research, promote academic integrity, and deter plagiarism. * To set up a system and set up a mechanism to detect and prevent plagiarism 6.Levels of Plagiarism & Penalty: Plagiarism percentage in various subjects may vary in research. Some software support multiple file formats and various languages like Copyleaks, Viper, etc., while others have additional features like proofreader & grammar check, vocabulary builder, etc. In the fight against plagiarism in an academic/ research Institution, educate and create awareness among students, teachers, scientists, and educate them about the types of plagiarism and to identify the plagiarism. [...]they must use a three-step process to fight against plagiarism, which involves taking steps before, during, and after creating the research[14]' Use the online plagiarism checker software before submitting the thesis, dissertation, and manuscripts and carefully cite the source. 12. The librarian may have additional roles in the context of prevention of plagiarism, as mentioned below: * Conducting orientation program for the researchers, students, scientists, staff, teachers, etc. * Organize seminars/ workshops and lectures from time to time for the users and Library professions. * Purchase of anti-plagiarism software to the users at the institute level. 13.